Tingkat Parasitisasi Berbagai Parasitoid Telur Nezara viridula L. pada Tanaman Kedelai - Jauharlina Jauharlina; Husni Husni; Bintra Mailina (Fakultas Pertanian, Universitas Syiah Kuala, 2008)
The Parasitism Level of Various Egg Parasitoids Associated with Nezara viridula L. on Soybean PlantationABSTRACT. It is well known that the presence of various egg parasitoids on the green stink bug, Nezara viridula, can decrease the population of this insect pest on soybean plantation. A research has been conducted to observe the parasitism level of various egg parasitoids associated with N. viridula on different stages of soybean plantation. The plant stages used were 4-5, 6-7, 8-9, and 10-12 weeks after planting (WAP), with 6 experimental plot for each stage, and 5 plants for each experimental unit. Three pairs of N. viridula adult then were relased onto each plant which was covered by the gauze cage earlier. When egg were laid, the cage was taken out leaving 2 eggs rafts per plant. These N. viridula eggs then were exposed to parasitoid for three days, before taking them all to the laboratory. The observations were done on the parasitized eggs. The result showed that different stages of soybean plants significantly affected the parasitism level of various egg parasitoids, with 26 to 46% parasitism level. Up to 71.8% of parasitize egg successfully became adult parasitoids. There were four different Hymenoptera egg parasitoids found associated with N. viridula, namely Telenomus sp. (Scelionidae), Gryon sp. (Scelionidae), Mycroteris sp. (Encyrtidae), and Anastatus sp. (Eupelmidae). Due to its abunden (91.5%) on soybean plantation, and its fair sex ratio, Telenomus sp.is believed to have a great potential for future development as a biological control agent on the green stink bug, N. viridula.